The Development Strategies of Cocoa Cultivation (Theobroma cacao L.) in Soppeng District. Issue 1 (November 2021) - Asrul, L; Yulianti, A; Musa, Y; Trisnaputri, AC
Abstract: The development of cocoa cultivation is currently optimal in Soppeng Regency and is still experiencing problems or problems such as managing recommended cocoa plants due to limited knowledge of farmers, increasing pests and diseases caused by improper application of cultivation systems, and erratic seasonal changes., the condition of plants that are old or damaged, resulting in unproductive plants. These factors greatly affect the life and welfare of cocoa farmers. This study aims to identify factors that support farmers in developing cocoa cultivation in Soppeng Regency and analyze business strategies for developing cocoa cultivation at the farmer level in Soppeng Regency. The study showed that the Internal Factor Strategy Analysis Matrix (IFAS) for developing cocoa cultivation consisted of the highest strength factor in the appropriate agro-climate conditions, supportive natural resources and the experience and skills of farmers in cocoa farming. Meanwhile, the highest weakness factor is the application of cocoa management that is not according to recommendations. The External Factor Strategy Analysis Matrix (EFAS) measures the opportunity factor of local government support to make cocoa a leading commodity in the plantation sector and education and training through field schools. Meanwhile, the highest factor is the factor of pests and plant diseases. Based on the SWOT diagram analysis, the results obtained coordinates 0.67; 2, 17, where these coordinates are in Quadrant I, which is an aggressive strategy, where this strategy can be used in developing cocoa cultivation in Soppeng Regency, namely utilizing the support provided by the government by increasing cocoa farming from upstream to downstream, doing extension and training in applying technology to farmers, creating demonstration plots based on agro-climatic conditions and available natural resources as training sites for cocoa farmers.